Transcriptomic and metabolomic reveals silicon enhances adaptation of rice under dry cultivation by improving flavonoid biosynthesis, osmoregulation, and photosynthesis - Jiang, Hao; Song, Ze; Su, Qing-Wang; Wei, Zhi-Heng; Li, Wan-Chun; Jiang, Zi-Xian; Tian, Ping; Wang, Zhen-Hui; Yang, Xue; Yang, Mei-Ying; Wei, Xiao-Shuang; Wu, Zhi-Hai (Frontiers in Plant Science, 2022)
Dry cultivation is a new rice crop mode used to alleviate water shortage and develop water-saving agriculture. There is obvious genetic difference compared with drought-tolerant rice. Silicon (Si) plays an important role in plant adaptation to adverse environmental conditions and can significantly improve the drought tolerance and yield of rice. However, the regulatory mechanism via which Si provides plant tolerance or adaptation under dry cultivation is not well understood. The present study investigated the changes in plant growth, photosynthetic gas exchange, and oxidative stress of the rice cultivar ‘Suijing 18’ under dry cultivation. Si improved photosynthetic performance and antioxidant enzyme activity and subsequently reduced lipid peroxidation of rice seedlings. Further, transcriptomics combined with quasi-targeted metabolomics detected 1416 and 520 differentially expressed genes (DEGs), 38 and 41 differentially accumulated metabolites (DAMs) in the rice leaves and roots, respectively. Among them, 13 DEGs were involved in flavonoid biosynthesis, promoting the accumulation of flavonoids, anthocyanins, and flavonols in the roots and leaves of rice under dry cultivation. Meanwhile, 14 DEGs were involved in photosynthesis, promoting photosystem I and photosystem II responses, increasing the abundance of metabolites in leaves. On the other hand, 24 DAMs were identified involved in osmoregulatory processes, significantly increasing amino acids and carbohydrates and their derivatives in roots. These results provide new insight into the role of Si in alleviating to adverse environmental, Si enhanced the accumulation of flavonoids and osmoregulatory metabolites, thereby alleviating drought effect on the roots. On the other hand, improving dehydration resistance of leaves, guaranteeing normal photosynthesis and downward transport of organic matter. In conclusion, Si promoted the coordinated action between the above-ground and below-ground plant parts and enhancing rice adaptability under dry cultivation conditions. The establishment of the system for increasing the yield of rice under dry cultivation provides theoretical and technical support thereby promoting the rapid development of rice in Northeast China, and ensuring national food security.